2017
DOI: 10.1097/bpo.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonoperative Pediatric Medial Humeral Epicondyle Fractures With and Without Associated Elbow Dislocation

Abstract: Level II-systematic review of level-II or level-I studies with inconsistent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 29 publications
2
19
0
4
Order By: Relevance
“…10 A review article by Kapok et al titled as outcomes of non-operative treatment of medial epicondyle fractures in children with and without associated elbow dislocation opined that increased rates of non-union, stiffness and elbow laxity may be associated with nonsurgical treatment of fractures with dislocation and needed further validated studies. 11 Our study indirectly proves the point raised by this study. We showed that clinical results are excellent when medial epicondyle fractures are surgically fixed even in cases of associated dislocation.…”
Section: Discussionsupporting
confidence: 75%
“…10 A review article by Kapok et al titled as outcomes of non-operative treatment of medial epicondyle fractures in children with and without associated elbow dislocation opined that increased rates of non-union, stiffness and elbow laxity may be associated with nonsurgical treatment of fractures with dislocation and needed further validated studies. 11 Our study indirectly proves the point raised by this study. We showed that clinical results are excellent when medial epicondyle fractures are surgically fixed even in cases of associated dislocation.…”
Section: Discussionsupporting
confidence: 75%
“…Operative fixation has been found to be superior to non-operative treatment in cases of medial epicondyle fracture among patients with elbow dislocation according to a recent study of 498 patients [22]. Regardless of fracture union rate, clinical or functional disabilities seem to be minimal after non-operative treatment of medial epicondyle fracture with or without associated elbow dislocation [8]. In general, the aim of operative treatment in cases of elbow dislocation with an associated fracture is to maximize an early return to daily mobilization and high-level activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…As another weakness, the fractures were diagnosed by radiographs, possibly resulting in the fact that not all osteochondral fractures were found. Magnetic resonance imaging was not performed in the cohort [25] due to practical reasons [8]. As a strength, this is the only study concerning the incidence and recent trend in childhood elbow dislocation in a normal child population since the 1980s, to best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medial epikondil kırıklarının tedavisi güncel literatürde halen tartışılmaktadır (3,(5)(6)(7)(8). Açık kırıklar ve medial epikondilin dirsek eklem içine inkarserasyonu cerrahi için kesin endikasyonlar olarak bildirilmiştir (1,2).…”
Section: Introductionunclassified